Detection of urine lipoarabinomannan is associated with proinflammatory innate immune activation, impaired host defense, and organ dysfunction in adults with severe HIV-associated tuberculosis in Uganda - Matthew, J. Cummings; Bakamutumaho, Barnabas; Komal, Jain; Adam Price; Owor, Nicholas; Kayiwa, John; Namulondo, Joyce; Byaruhanga, Timothy; Muwanga, Moses; Nsereko, Christopher; Nayiga, Irene; Kyebambe, Stephen; et al. (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2023)
Background: The immunopathology of disseminated HIV-associated tuberculosis (HIV/TB), a leading cause of critical illness and death among persons living with HIV in sub-Saharan Africa, is incompletely understood. Reflective of hematogenously disseminated TB, detection of lipoarabinomannan (LAM) in urine is associated with greater bacillary burden and poor outcomes in adults with HIV/TB. Methods: We determined the relationship between detection of urine TB-LAM, organ dysfunction, and host immune responses in a prospective cohort of adults hospitalized with severe HIV/TB in Uganda. Generalized additive models were used to analyze the association between urine TB-LAM grade and concentrations of 14 soluble immune mediators. Whole-blood RNA-sequencing data were used to compare transcriptional profiles between patients with high- vs. low-grade TB-LAM results. Results: Among 157 hospitalized persons living with HIV, 40 (25.5%) had positive urine TB-LAM testing. Higher TB-LAM grade was associated with more severe physiologic derangement, organ dysfunction, and shock. Adjusted generalized additive models showed that higher TB-LAM grade was significantly associated with higher concentrations of mediators reflecting proinflammatory innate and T-cell activation and chemotaxis (IL-8, MIF, MIP-1β/CCL4, and sIL-2Ra/sCD25). Transcriptionally, patients with higher TB-LAM grades demonstrated multifaceted impairment of antibacterial defense including reduced expression of genes encoding cytotoxic and autophagy-related proteins and impaired cross-talk between innate and cell-mediated immune effectors. Conclusions: Our findings add to emerging data suggesting pathobiological relationships between LAM, TB dissemination, innate cell activation, and evasion of host immunity in severe HIV/TB. Further translational studies are needed to elucidate the role for immunomodulatory therapies, in addition to optimized anti-TB treatment, in this often critically ill population.